2000
DOI: 10.1038/sj.onc.1203225
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β2 inhibition of Hepatocyte Growth Factor-induced endothelial proliferation and migration

Abstract: Angiogenesis is a highly controlled event which depends on the proper equilibrium of activators and inhibitors present within the microenvironment. Hepatocyte Growth Factor (HGF) activates migration and proliferation of endothelial cells and is angiogenic, acting through the tyrosine kinase receptor encoded by the Met protooncogene. To get insights into the molecular mechanisms involved in HGF-induced angiogenesis, we searched for cDNAs di erentially expressed in human endothelial cells exposed to HGF, a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…49 Inhibition of retinal angiogenesis by interruption of TSP-1's activation of TGF-␤ 50 suggests that bioactivation of TGF-␤ may be one mechanism responsible for TSP-1-induced antiangiogenesis. An antiangiogenic function in vivo was suggested for TGF-␤2 based on its inhibitory effect on hepatocyte growth factor-mediated angiogenesis, 51 whereas experimental evidence suggests that TGF-␤1 has proangiogenic 52 and proapoptotic effects. 53,54 Since TGF-␤2 is only minimally expressed in vascular endothelium under normoxic conditions, 55,56 the degree to which hypoxic induction of TGF-␤2, as distinct from TGF-␤1 or TGF-␤3, is associated with regulation of apoptosis and angiogenesis in endothelium has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…49 Inhibition of retinal angiogenesis by interruption of TSP-1's activation of TGF-␤ 50 suggests that bioactivation of TGF-␤ may be one mechanism responsible for TSP-1-induced antiangiogenesis. An antiangiogenic function in vivo was suggested for TGF-␤2 based on its inhibitory effect on hepatocyte growth factor-mediated angiogenesis, 51 whereas experimental evidence suggests that TGF-␤1 has proangiogenic 52 and proapoptotic effects. 53,54 Since TGF-␤2 is only minimally expressed in vascular endothelium under normoxic conditions, 55,56 the degree to which hypoxic induction of TGF-␤2, as distinct from TGF-␤1 or TGF-␤3, is associated with regulation of apoptosis and angiogenesis in endothelium has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, suramin may induce Src activation by blocking TGF-␤ binding to its receptor. In this context, it has been reported that TGF-␤ treatment decreases Src activity and cell growth in the prostate carcinoma cell line PC3 and hepatoma cell line HepG2 (Atfi et al, 1994;Fukuda et al, 1998) and prevents hepatocyte growth factorinduced tyrosine phosphorylation of Src and migration in endothelial cells (Manganini and Maier, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that TGF-␤2 gene is specifically induced after infection of HUVECs with an adenovirus gene transfer vector that confers prolonged survival to endothelial cells even in the absence of serum. 77 Furthermore, exposure of endothelial cells to TGF-␤2 was shown to counteract the angiogenic effects of hepatocyte growth factor via inhibition of its signaling, 78 and antibody to TGF-␤2 was shown to stimulate DNA synthesis in pericytes. 79 Based on these and previous findings regarding the antiinflammatory role of the TGF-␤ family of cytokines, 75,[80][81][82] we hypothesize that TGF-␤2 induces an antiproliferative, antiapoptotic, and antiangiogenic signal to mitigate the inflammatory signals induced by hypoxia and augments an adaptive response in the endothelium.…”
Section: Discussionmentioning
confidence: 99%